2004
DOI: 10.1128/aem.70.5.3167-3170.2004
|View full text |Cite
|
Sign up to set email alerts
|

Albusin B, a Bacteriocin from the Ruminal Bacterium Ruminococcus albus 7 That Inhibits Growth of Ruminococcus flavefaciens

Abstract: An ϳ32-kDa protein (albusin B) that inhibited growth of Ruminococcus flavefaciens FD-1 was isolated from culture supernatants of Ruminococcus albus 7. Traditional cloning and gene-walking PCR techniques revealed an open reading frame (albB) encoding a protein with a predicted molecular mass of 32,168 Da. A BLAST search revealed two homologs of AlbB from the unfinished genome of R. albus 8 and moderate similarity to LlpA, a recently described 30-kDa bacteriocin from Pseudomonas sp. strain BW11M1.Ruminococcus al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Previous work reported the production of albusin B by R. albus 7 and R. albus 8, and two new R. albus strains whose genomes encode albusin-like bacteriocins were identified in this study. Albusin B was initially described to be a relatively hydrophilic, heatlabile, high-molecular-mass (Ͼ30 kDa) protein showing a narrow range of antibacterial activity (29). The putative class III bacteriocins in R. albus AD2013 and R. albus SY3 had identical amino acid sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work reported the production of albusin B by R. albus 7 and R. albus 8, and two new R. albus strains whose genomes encode albusin-like bacteriocins were identified in this study. Albusin B was initially described to be a relatively hydrophilic, heatlabile, high-molecular-mass (Ͼ30 kDa) protein showing a narrow range of antibacterial activity (29). The putative class III bacteriocins in R. albus AD2013 and R. albus SY3 had identical amino acid sequences.…”
Section: Discussionmentioning
confidence: 99%
“…5). The amino acid sequence of albusin B from R. albus 7 has been described (29), and linocin was previously reported to be a putative class III bacteriocin produced by W. succinogenes DSM 1740, as determined using in silico analysis (30). Nonetheless, the analysis of the R. albus 7 genome revealed the genetic organization of the albusin B gene cluster, demonstrating the presence of an ABC transporter adjacent to albusin B and two ORFs encoding putative transposases related to the IS1595 and IS66 families.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and coworkers identified such an MMBL domain in a 32-kDa bacteriocin (albusin B or AlbB) produced by the ruminal bacterium Ruminococcus albus strain 7. They showed that albusin B is a potent growth inhibitor of Ruminococcus flavescens strains (11). Albusin B and LlpA BW11M1 are likely released from the bacteriocinogenic cells via a different route.…”
mentioning
confidence: 99%
“…The mechanism by which this type of bacteriocin inhibits the growth of sensitive bacteria is still under investigation. Despite the presence of MMBL domains, LlpA and albusin B are unable to bind mannose (11,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation